2004
DOI: 10.1074/jbc.m403545200
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Structural Rearrangement of the Cytoplasmic Pore during Activation of the 5-HT3A Receptor

Abstract: Ligand-gated ion channel receptors mediate the response of fast neurotransmitters by opening in less than a millisecond. Here, we investigated the activation mechanism of a serotonin-gated receptor (5-HT 3A ) by systematically introducing cysteine substitutions throughout the pore-lining M1-M2 loop and M2 transmembrane domain. We hypothesized that multiple cysteines in the narrowest region of the pore, which together can form a high affinity binding site for metal cations, would reveal changes in pore structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…5A Right) is wider at its bottom and narrower at its upper part. Yet, the cytoplasmic vestibule remains the narrowest part of the pore in both the closed and the open states, in accord with Panicker et al (17). Our open-pore structure is compatible with the inability of Zn 2ϩ to block chimera Hϩ16Ј and with the capacity of Zn 2ϩ to block the open channel and to produce off responses by interacting specifically with histidines substituted at position Ϫ5Ј, Ϫ2Ј, Ϫ1Ј, 2Ј, or 9Ј (Table 1 and Fig.…”
Section: Functional and Structural Implications Of The Off-response Csupporting
confidence: 75%
“…5A Right) is wider at its bottom and narrower at its upper part. Yet, the cytoplasmic vestibule remains the narrowest part of the pore in both the closed and the open states, in accord with Panicker et al (17). Our open-pore structure is compatible with the inability of Zn 2ϩ to block chimera Hϩ16Ј and with the capacity of Zn 2ϩ to block the open channel and to produce off responses by interacting specifically with histidines substituted at position Ϫ5Ј, Ϫ2Ј, Ϫ1Ј, 2Ј, or 9Ј (Table 1 and Fig.…”
Section: Functional and Structural Implications Of The Off-response Csupporting
confidence: 75%
“…1C, for the conserved Val291 residue of the 5-HT 3A receptor, the present and previous studies have also shown that mutations of Val291 to other amino acids affect the inhibition of I 5-HT in response to anesthetics, cadmium, ginsenoside Rg 3 and TMB-8. 3,4,7,8,18) Thus, Val291 of the 5-HT 3A receptor could be useful targets for studying the receptor-related pharmacology. This residue could also be used for drug developments such as anti-emetic agent if diltiazem or TMB-8 derivatives are selective for 5-HT 3A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we hypothesized that there are common interaction site(s) with diltiazem and TMB-8. Since TM2 forms the pore region of 5-HT 3A receptors, and mutations in this region affect the inhibition of I 5-HT in response to anesthetics, cadmium and the open channel blocker, 3,4,7) we investigated the effect of diltiazem and TMB-8 on I 5-HT in oocytes expressing 5-HT 3A receptors that contain site- Table 1 (meanϮS.E.M. ; nϭ9-12 oocytes for each point).…”
Section: Effect Of Diltiazem and Tmb-8 On I 5-ht In Oocytes Expressinmentioning
confidence: 99%
“…Evidence from SCAM has indicated that the intracellular end of M1 and the M1-M2 linker lie along the path of the permeating ions, and these regions contain residues responsible for anion/ cation selectivity (Filippova et al 2004 ; also see section 4.4). Coordination of cadmium ions in 5-HT 3 R Cys mutants and the use of negatively and positively charged thiol reactive MTS reagents have demonstrated that residues in the M1-M2 loop are accessible (Panicker et al 2002(Panicker et al , 2004.…”
Section: (2009)mentioning
confidence: 99%